Value analysis and engineering reengineered the blueprint for achieving operational excellence and developing problem solvers and innovators - Kassa, Abate O. (CRC Press, 2016)
you are engaged in the pursuit of excellence and are ready to make the leap from good to great while generating an immediate payback, you will want to empower your people with an understanding of the reengineered VA/VE outlined in this book